Growth response and ionic regulation in common carp (Cyprinus carpio L.) after chronic dietary copper exposure and recovery - Ajani, E. K; Akpoilih, B. U (Advances in Aquaculture and Fisheries Management, 2020)
Effects of exposure of common carp juveniles (Cyprinus carpio L.) to dietary copper and its recovery rate were investigated with the aim of determining the growth and physiological impact. The fish were fed elevated copper diets (1000 and 2000 mgCukg-1 as diet 2 and diet 3 respectively) and control diet (5 mgCukg- , as diet 1) for 42days and were then fed the control diet for a further 21days. After 42days of exposure to elevated copper diets, growth performance examined showed that there was significant increase at (p<0.05) in feed intake, %body weight, weight gain and condition factor by fish fed diet 2 compared to diet 1 and diet 3. There was, however, no difference in specific growth rate, feed conversion ratio, in all treatments (p>0.05). Hepatosomatic index increased significantly in fish fed both elevated diets compared to control diet (p<0.05). Recovery period on normal diet (control) showed no significant effect of copper recovery on fed intake, weight gain, %body weight, specific growth rate and feed conversion ratio in all treatments (p>0.05), but, fish fed diet 2 showed a significant reduction in condition factor compared to other diets (p<0.05). Tissue Na+ , Ca2+ K + were disturbed throughout the experiment with sodium increasing from 257.82±2.50 to 388.14±1.32 mol/g and calcium increasing from 499.54±6.81to 1025.94±9.16molg-1 reducing gill copper from 11.63±0.37to 0.00±0.00 mgCukg-1 . Intestinal copper decreased from 14.93 ±0.1 to 0.00±0.00 mgCukg-1 as a result of sodium increasing from 130.30±5.12 to 438.72±2.44 molg-1 . Increased gill copper of the 1000 mgCukg-1 diet exposed fish during exposure compared to the control was due to copper induced decrease in plasma ion regulatory sodium (Na ATPase activity), which protected fish from direct toxicity effect and could also suggest another pathway other than the common Na/Cu apical channel shared between sodium and copper through which copper binds to fish gill; diet 2 fish showing significant increase at (p<0.05) in haematocrit, red blood cell, white blood cell and neutrophil, and a significant reduction in lymphocyte and mean cell haemoglobin compared to diet 1 and diet 3, (p<0.05). This increase in blood indices is indicative of stress onset to which fish fed diet 2 is subjected. Fish fed diet 3 showed significant reduction in haematocrit, red blood cell, white blood cell and increased lymphocyte (p<0.05) and became anaemic with severe skin discoloration, indicative of a worsening effect of excess dietary copper exposure on the fish. There were no significant differences in moisture content of all tissues during and after copper exposure (p<0.05). Gills of fish fed diet 3 increased post-exposure, indicative of protection of the structural integrity of the gill to prevent hypoxia through oxygen supply from water